Petrology and geochemistry of the orbicular granitoid of Sierra de Velasco (NW Argentina) and implications for the origin of orbicular rocks - Grosse, Pablo (2010)
The Velasco orbicular granitoid is a small (65 × 15 m), irregularly-shaped body that cropsout within the Huaco granite, central Sierra de Velasco, NW Argentina. It consists of ellipsoid-shapedorbicules of 3 to 15 cm length immersed in an aplitic to pegmatitic matrix. The orbicules are formedby a core made up of a K-feldspar megacryst, partially to totally replaced by plagioclase, an inner shellof radial and equant plagioclase crystals, a layer of tangentially oriented biotite laths, and an outer shellof plumose plagioclase crystals, containing diffuse rings of tangentially oriented biotite. The orbiculargranitoid formed in situ in a pocket of evolved and volatile-rich melt segregated from the surroundingpartially crystallized Huaco granite, possibly via a filter pressing mechanism. The segregated meltentrained relatively few K-feldspar megacrysts into the pocket, leaving behind a concentration ofmegacrysts around the pocket. High water concentration caused effective superheating of the meltand destruction of nuclei, with only the large megacrysts surviving as solids. Sudden water-pressureloss and exsolution of the volatile phase, perhaps related to a volcanic eruption or fracturing of thesurrounding granite, caused rapid undercooling of the melt. The orbicules grewin the undercooled meltby heterogeneous nucleation on the megacrysts, which acted as nucleation seeds, and crystallizationof reversely zoned radial plagioclase and sporadic crystallization of tangential biotite rings accordingto fluctuations in its saturation. Orbicular growth gave way to crystallization of the equiaxial interorbicularmatrix in two stages, when sufficient polymerization of the melt was attained. The time scaleof formation of the orbicular granitoid was fast, possibly a matter of a few weeks or months.